Motywacja do pomagania współpracownikom - Haromszeki, Łukasz (Co-Worker Help Motivation, 2008)
In the article, the author shows and analyzes results of the research on prosocial motivation. He presents necessary conditions for the appearance of prosocial behaviour in certain situations. In the next part of the article, the author describes outcomes of the international survey concerning the topic of helping people in work. Afterwards, the author presents and analyzes findings of own research regarding prosocial inclinations of employees in the selected enterprises of Lower Silesia.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 230-243